2000
DOI: 10.1074/jbc.275.10.6975
|View full text |Cite
|
Sign up to set email alerts
|

Building a Thermostable Membrane Protein

Abstract: The poor stability of membrane proteins in detergent solution is one of the main technical barriers to their structural and functional characterization. Here we describe a solution to this problem for diacylglycerol kinase (DGK), an integral membrane protein from Escherichia coli. Twelve enhanced stability mutants of DGK were obtained using a simple screen. Four of the mutations were combined to create a quadruple mutant that had improved stability in a wide range of detergents. In n-octylglucoside, the wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
142
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 20 publications
(22 reference statements)
6
142
3
Order By: Relevance
“…This was subsequently demonstrated for two bacterial proteins, diacylglycerol kinase (5, 6) and bacteriorhodopsin (7). Random mutagenesis of diacylglycerol kinase identified specific point mutations that increased thermostability, and, when combined, the effect was additive so that the optimally stable mutant had a half-life of 35 min at 80°C compared with a half-life of 6 min at 55°C for the native protein (6). A further study on bacteriorhodopsin by cysteine-scanning mutagenesis along helix B demonstrated that it was not possible to predict which amino acid residues would lead to thermostability upon mutation, nor, when studied in the context of the structure, was it clear why thermostabilization had occurred (7).…”
mentioning
confidence: 99%
“…This was subsequently demonstrated for two bacterial proteins, diacylglycerol kinase (5, 6) and bacteriorhodopsin (7). Random mutagenesis of diacylglycerol kinase identified specific point mutations that increased thermostability, and, when combined, the effect was additive so that the optimally stable mutant had a half-life of 35 min at 80°C compared with a half-life of 6 min at 55°C for the native protein (6). A further study on bacteriorhodopsin by cysteine-scanning mutagenesis along helix B demonstrated that it was not possible to predict which amino acid residues would lead to thermostability upon mutation, nor, when studied in the context of the structure, was it clear why thermostabilization had occurred (7).…”
mentioning
confidence: 99%
“…Accurate assessments of their thermodynamic stability will also aid in the design of more stable membrane proteins for therapeutic applications and for structural studies of this structurally underrepresented class of proteins. For example, overcoming conformational dynamics has been a major breakthrough in the recent determination of the structure of lactose permease (10) and superstable mutants of diacylglycerolkinase have dramatically improved crystallization and NMR conditions (11,12). Unfortunately, quantitative studies of membrane protein stability have been hampered by difficulties to completely and reversibly unfold these proteins (13,14).…”
mentioning
confidence: 99%
“…Site-directed mutagenesis was used by Bowie and coworkers to improve the stability of two bacterial membrane proteins (11)(12)(13). Rhodopsin has also been stabilized by 10°C, although in this case a disulfide bond was engineered between the N terminus and the third extracellular loop based on structural data (14).…”
mentioning
confidence: 99%